A rubidium vapor source for a plasma source for AWAKE. (15th December 2017) - Plyushchev, G; Kersevan, R; Petrenko, A; Muggli, P
Abstract: We present the scheme for a rubidium vapor source that is used as a plasma source in the AWAKE plasma wakefield acceleration experiment. The plasma wakefield acceleration process requires a number of stringent parameters for the plasma: electron density adjustable in the (1–10)  ×  10 14 cm −3 range, 0.25% relative density uniformity, sharp (<10 cm) density ramps at each end, density gradient adjustable from  −3 to + 10 % over 10 m, and %-level density step near the beginning the plasma column. We show with analytical and direct simulation Monte Carlo results that the rubidium density in the proposed source should meet these requirements. Laser ionization then transfers the above neutral vapor parameters to the plasma.